2021
DOI: 10.1073/pnas.2024102118
|View full text |Cite
|
Sign up to set email alerts
|

An intracellular nanobody targeting T4SS effector inhibits Ehrlichia infection

Abstract: Infection with obligatory intracellular bacteria is difficult to treat, as intracellular targets and delivery methods of therapeutics are not well known. Ehrlichia translocated factor-1 (Etf-1), a type IV secretion system (T4SS) effector, is a primary virulence factor for an obligatory intracellular bacterium, Ehrlichia chaffeensis. In this study, we developed Etf-1–specific nanobodies (Nbs) by immunizing a llama to determine if intracellular Nbs block Etf-1 functions and Ehrlichia infection. Of 24 distinct an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 50 publications
0
22
0
1
Order By: Relevance
“…Moreover, in similar experiments with yeast, Etf-1 also localized to mitochondria and inhibited apoptosis induced by heterologous expression of human Bax (Liu et al, 2012). The N-terminal 24 amino-acid residues of Etf-1, especially residue K23, play a critical role in mitochondrial targeting of Etf-1, as deletion mutation of this residue significantly decreased Etf-1 localization to mitochondria (Zhang et al, 2021). The mitochondrial matrix protein manganese superoxide dismutase (MnSOD) maintains a basal level of ROS in cells by scavenging O − 2 and is essential for maintaining aerobic life (Holley et al, 2012).…”
Section: Etf-1 Inhibits Host-cell Apoptosismentioning
confidence: 69%
See 1 more Smart Citation
“…Moreover, in similar experiments with yeast, Etf-1 also localized to mitochondria and inhibited apoptosis induced by heterologous expression of human Bax (Liu et al, 2012). The N-terminal 24 amino-acid residues of Etf-1, especially residue K23, play a critical role in mitochondrial targeting of Etf-1, as deletion mutation of this residue significantly decreased Etf-1 localization to mitochondria (Zhang et al, 2021). The mitochondrial matrix protein manganese superoxide dismutase (MnSOD) maintains a basal level of ROS in cells by scavenging O − 2 and is essential for maintaining aerobic life (Holley et al, 2012).…”
Section: Etf-1 Inhibits Host-cell Apoptosismentioning
confidence: 69%
“…To verify the functions of intracellular Etf-1 and investigate the possibility that Etf-1 could be used as a therapeutic target, Etf-1−specific nanobodies were developed by immunizing a llama (Zhang et al, 2021). One particular nanobody could form a stable complex with Etf-1 and thereby block the mitochondrial localization of Etf-1 (Zhang et al, 2021).…”
Section: Etf-1 Inhibits Host-cell Apoptosismentioning
confidence: 99%
“…Extensive research has demonstrated that nanobodies play a significant role in several inflammatory diseases. [44][45][46] In related experiments, nanobodies specific to TLR4 treatment significantly decreased mRNA and protein levels of proinflammatory cytokines in NR8383 cells. 47 Consistently with that research, our in vitro tests showed that compared with negative nanobody treatment, specific nanobody treatment significantly suppressed mRNA and protein expression of IL1β and IL6 in HCECs stimulated by A. fumigatus.…”
Section: Effects Of Nanobodies On Proliferation Of Hcecsmentioning
confidence: 91%
“…RF/6A monkey endothelial cells (ATCC) were used in immunofluorescence labeling for unambiguous localization analysis owing to their tight adherence and thinly spread morphology ( 5 ). Human embryonic kidney HEK293T cells (ATCC) were used for transfection and pulldown assays, as they can be transfected with high efficiency ( 41 ).…”
Section: Methodsmentioning
confidence: 99%